Evaluation of classroom-based online multimedia language assessment - Cetinić, Ana; Seljan, Sanja (2011)
Implementation of on-line multimedia language assessment represents a domain of high interest, although in Croatia it is still in the beginning phase. It could be used as summative testing at the end of education cycle or lesson, as formative testing during the education period, as diagnostic testing usually at the beginning of education period, i.e. as self-evaluation or peer assessment method. Bloom points out six levels of cognitive learning (including fact knowledge, understanding, implementation, analysis, synthesis and evaluation), skills and attitudes, which are to be covered by the assessment process. Having certain advantages, but also disadvantages, the best results are obtained as complementary method with traditional assessment and in combination with other types of assessment as oral communication, individual research, group work, tandem learning, etc. For the purpose of evaluation of on-line multimedia language assessment, the research was conducted at the Faculty of Humanities and Social Sciences, University of Zagreb among the group of 29 Croatian students studying the Italian language. The online multimedia test was implemented using Omega (Croatian version of Moodle LMS system) containing 21 questions relating to the Italian language and culture. Questions were accompanied by various types of multimedia – audio file, video clip and a map of Italy. The test covered knowledge, as well as listening, reading and writing skills, while speaking skills were not covered. After the test, students were asked to fill out a questionnaire to express affective attitudes. The results of the test and of the have been analyzed. At the end, the guidelines for further researches are suggested.
Projekt MZOS
ENG